Pengembangan media berbasis prezi pada mata pelajaran sejarah kelas X SMA dengan model 4d - Prasetyo Nur Rohman; Mohammad Na’im; Sumardi Sumardi (University of Muhammadiyah Malang, 2021)
Students’ low interest in History is a common problem to many teachers. Prezi was hypothesized to increase students’ interest in learning History. This study aims to develop a Prezi-based program through a 4D model for History subjects taught to the 10th graders (first graders of High School). It employed observation and questionnaire methods. Participants of this study were students of SMA Muhammadiyah 1 Jember, SMA Muhammadiyah 2 Jember, and SMA Muhammadiyah 3 Jember. The data analysis involved learning material, media, and design validation. Results show that the first stage design was 81%, categorized as good; while the second stage design was 92%, categorized as very good. Results of the first stage material expert validation obtained 62%m categorized as poor; and the second validation obtained 77%, categorized as good. These findings indicate that Prezi-based media development is feasible and effective as a medium for learning History.